A 'long-fuse domestication' of the horse? Tooth shape suggests explosive change in modern breeds compared with extinct populations and living Przewalski's horses. (August 2016) - Seetah, Krish; Cardini, Andrea; Barker, Graeme
Archaeological and molecular data suggest that horses were domesticated comparatively recently, the genetic evidence indicating that this was from several maternal haplotypes but only a single paternal one. However, although central to our understanding of how humans and environmental conditions shaped animals during domestication, the phenotypic changes associated with this idiosyncratic domestication process remain unclear. Using geometric morphometrics on a sample of horse teeth including Pleistocene wild horses, modern Icelandic and Thoroughbred domestic horses, Przewalski's wild horses of recent age and domestic horses of different ages through the Holocene, we show that, despite variations in size likely related to allometry (changes to bone size in proportion to body size), natural and artificial selective pressures and geographic and temporal heterogeneity, the shape of horse teeth has changed surprisingly little over thousands of years across Eurasia: the shapes of the premolars of prehistoric and historic domestic horses largely resemble those of Pleistocene and recent wild horses. However, this changed dramatically after the end of the Iron Age with an explosive increase in the pace and scale of variation in the past two millennia, ultimately resulting in a twofold jump in the magnitude of shape divergence in modern breeds. Our findings indicate that the pace of change during domestication may vary even within the same structure with shape, but not size, suggesting a 'long-fuse' model of phenotypic modification, where an initial lengthy period of invariance is followed by an explosive increase in the phenotypic change. These observations support a testable model that is applicable to other traits and species and add a new layer of complexity to the study of interactions between humans and the organisms they domesticated.